Calculation:

Consider the following function

\(\displaystyle{g{{\left({x}\right)}}}={2}{x}+{4}\)

For x-intercept put \(\displaystyle{g{{\left({x}\right)}}}={0}\)

\(\displaystyle{0}={2}{x}+{4}\)

\(\displaystyle{2}{x}=-{4}\)

\(\displaystyle{x}=-{2}\)

Hence, the x-intercept is at (-2, 0)

For y-intercept put \(\displaystyle{x}={0}\)

\(\displaystyle{g{{\left({0}\right)}}}={2}{\left({0}\right)}+{4}={4}\)

Hence, the y-intercept is at (0,4).

Consider the following function

\(\displaystyle{g{{\left({x}\right)}}}={2}{x}+{4}\)

For x-intercept put \(\displaystyle{g{{\left({x}\right)}}}={0}\)

\(\displaystyle{0}={2}{x}+{4}\)

\(\displaystyle{2}{x}=-{4}\)

\(\displaystyle{x}=-{2}\)

Hence, the x-intercept is at (-2, 0)

For y-intercept put \(\displaystyle{x}={0}\)

\(\displaystyle{g{{\left({0}\right)}}}={2}{\left({0}\right)}+{4}={4}\)

Hence, the y-intercept is at (0,4).